Clinical Characteristics at Initial Presentation and Impact of Dual Therapy on the Outcome of Bacteremic Streptococcus pneumoniae Pneumonia in Adults. Issue 8 (3rd December 2004) - Weiss, K; Low, DE; Cortes, L; Beaupre, A; Gauthier, R; Gregoire, P; Legare, M; Neoveu, F; Thibert, D; Tremblay, C
Abstract : BACKGROUND: Approximately 10% of patients hospitalized with community-acquired pneumonia (CAP) are bacteremic. Bacteremic Streptococcus pneumoniae pneumonia (BSPP) is the number one cause of mortality, representing up to 70% of all CAP deaths. In fact, all CAP guidelines have identified this issue as one of the most important issues when establishing their recommendations. OBJECTIVE: To assess the impact of dual antibiotic therapy in patients with BSPP. PATIENTS AND METHODS: All cases of BSPP in patients 18 years of age and older who were hospitalized from 1995 to 2000 were retrospectively analyzed. The standard initial therapeutic regimen used was cefuroxime with or without a macrolide from 1995 to 1997, and ceftriaxone and azithromycin or clarithromycin from 1998 to 2000. During the 1995 to 1997 period, only 16% of the patients initially received a macrolide, whereas all patients in the 1998 to 2000 period received a macrolide at admission. RESULTS: Ninety-five patients (49 men, 46 women) with a mean age of 63 years (range 20 to 98 years) were included in the present study. The mean pneumonia severity index at admission was 113 for the monotherapy cohort and 114 for the dual therapy group. At admission, 30.5% of patients had a leukocyte count greater than 20´109/L, 11.5% had a systolic blood pressure less than 90 mmHg, 44.2% had a respiratory rate greater than 30 breaths/min and 33.6% had nausea/vomiting, necessitating some form of therapy or preventing the patient from eating. In addition, 16.8% had no fever at admission. Overall, 72.5% became afebrile within 48 h. Fifteen (15.8%) patients died (four within the first 72 h). The mortality rate was significantly higher in the monotherapy group (11 of 42 patients; 25.6%) than in the dual therapy cohort (four of 53 patients; 7.5%) (OR 0.23; 95% CI 0.07 to 0.74). Antibiotic resistance was not associated with increased mortality. CONCLUSION: The combination of ceftriaxone plus a macrolide significantly reduced the mortality rate compared with monotherapy (cefuroxime) in patients with CAP that have the highest mortality rate.